Peliosanthes ligniradicis, a new species (Asparagaceae) from Arunachal Pradesh, NE India - Taram, Momang; Borah, Dipankar; Tanaka, Noriyuki (Phytotaxa, 2020)
A new species of Peliosanthes named P. ligniradicis from Arunachal Pradesh, NE India, is described and illustrated here. It somewhat resembles P. subspicata described from NE India, but is distinguishable by the thicker, stilt-like, semi-woody roots, somewhat elongate (sub) moniliform stem, ovate-oblong or oblong perianth segments, and basally hexagonal and  apically 6-crenate.